Level of Covid-19-Related Threats and Stress in Students in the Context of Their Personality Traits: Support Expected and Help Received - Godawa, Grzegorz; Gurba, Ewa; Kutek-Sładek, Katarzyna (Multidisciplinary Journal of School Education, 2023)
University studies during the COVID-19 pandemic are conditioned by many factors that evoke a sense of danger and stress. The purpose of the study was to investigate the situations during the COVID-19 pandemic perceived by students as threatening and to determine the relevance of students’ personality traits in their assessments of the threats and severity of stress associated with the COVID-19 pandemic. Another aim of the research was to identify from whom they most frequently expect help in such situations. The following research problems were formulated. 1. Which situations related to the COVID-19 pandemic are rated most and least threatening by students? 2. Which personality traits described in the ‘Big Five’ theory (McCrae & Costa, 1987) protect students from experiencing grave threats and from experiencing higher stress in the COVID-19 pandemic? 3. What sources of support are received by students and offered by the University?The study involved 149 first-year students of the Pontifical University of John Paul II in Krakow.  The survey was conducted in February 2021. The following research tools were used in the study: a short questionnaire for measuring the Big Five personality traits (IPIP-BFM-20), the Perceived Stress Scale (PSS-10) and the Questionnaire on Types of COVID-19-Related Threats (TCT).The results of the study showed the importance of: 1. selected personality traits, such as emotional stability, extroversion and conscientiousness, for students’ assessment of the threat to the individual, and protection against the severity of stress experienced; 2. social support that young people receive from their loved ones, including mainly mothers and friends, and 3. support provided by the University.